Effect of bicalutamide on serum total testosterone concentration in transgender adults: a case series - Lachlan M. Angus; Quoc Vinh Hong; Ada S. Cheung; Brendan J. Nolan (Therapeutic Advances in Endocrinology and Metabolism)
Background: There is interest in repurposing bicalutamide for gender-affirming hormone therapy, but little data regarding efficacy and safety in the transgender population. Objectives: To determine the effect of bicalutamide on serum total testosterone concentrations and liver function. Given bicalutamide is a pure androgen receptor antagonist, we hypothesized that serum total testosterone concentrations would be higher than the cisgender female reference range and those recommended for transgender individuals in consensus guidelines. Design: Case series. Methods: We identified transgender people attending outpatient clinics who were using bicalutamide for gender affirmation. The primary outcome was serum total testosterone concentration. Secondary outcomes included serum alanine transferase (ALT) concentration. Results: Twenty-four transfeminine people prescribed bicalutamide were identified. The median (interquartile range) age was 29 (24–38) years, bicalutamide dose 25 (25–50) mg daily and bicalutamide duration 6 (4–10) months. The median serum total testosterone concentration was 7.7 (0.7–17.5) nmol/L, luteinizing hormone 2.9 (0.5–6.0) IU/L and ALT 20 (13–29) IU/L. One individual had asymptomatic transaminitis. Six individuals discontinued bicalutamide due to a lack of perceived benefit. Conclusion: Bicalutamide was associated with significant variation in serum total testosterone concentration, likely related to concomitant estradiol or previous anti-androgen therapy. Median serum ALT concentrations remained within the normal reference range. Guideline recommendations for serum total testosterone within the cisgender female reference range may be inappropriate for people using bicalutamide. Further research is needed to establish the longer-term efficacy and safety of bicalutamide in the transfeminine population.